Strategi Penurunan Dampak Lingkungan pada Instalasi Pengolahan Air Minum di Kota Balikpapan dengan Metode Life Cycle Assessment (LCA) - Muhamad Nur Ibnu Luthfi Saud; Haifa Cahya Nabila Almunawar; Intan Dwi Wahyu Setyo Rini; Tasya Mirza Ratu Pattisahusiwa; Rizka Lestari (SPECTA Journal of Technology, 2025)
The clean water production process must be carried out effectively without harming the environment. The Regional Drinking Water Company (PDAM) Tirta Manuntung Balikpapan City produces clean water through several Drinking Water Treatment Plants (DWTP) such as Kampung Damai and Kilometer (KM) 8. Potential negative impacts can arise from the use of chemicals, processing methods and units, as well as high-power equipment. The Life Cycle Assessment (LCA) method can be used to systematically calculate the environmental impacts of an activity's input, process, and output. This study aimed to calculate the environmental impacts due to the production process at Kampung Damai DWTP and KM 8 DWTP of Balikpapan City using the LCA method, as well as formulate strategies to reduce negative impacts. The principle of this study was to calculate impacts using the ReCiPe 2016 model (midpoint H), based on software (SimaPro), with gate-to-gate data coverage (from the intake unit to the reservoir). The study's results found that every 1 m³ of production at Kampung Damai DWTP resulted in impacts in the form of human carcinogens (0.0179 pt), freshwater ecotoxicity (0.00329 pt), and freshwater eutrophication (0.00266 pt). Meanwhile, at KM 8, DWTP resulted in human carcinogenic impacts of 0.026 pt, freshwater ecotoxicity of 0.04 pt, and marine ecotoxicity of 0.03 pt. Alternative strategy to mitigate potential environmental impacts can be implemented through the substitution of aluminum sulfate (Al2SO4) chemicals with Poly Aluminum Chloride (PAC), which reduces human carcinogenicity by 28%, freshwater ecotoxicity by 12%, and freshwater eutrophication by 4% at Kampung Damai DWTP. Furthermore, substitution of chemicals with PAC and low-power electrical equipment can reduce human carcinogenicity by 8.38%, freshwater ecotoxicity by 14.09%, and marine ecotoxicity by 12.13% at KM 8 DWTP.